Early life stress as an influence on limbic epilepsy: an hypothesis whose time has come? - Koe, Amelia S.; Jones, Nigel C.; Salzberg, Michael R. (Frontiers in Behavioral Neuroscience, 2009)
The pathogenesis of mesial temporal lobe epilepsy (MTLE), the most prevalent form of refractory focal epilepsy in adults, is thought to begin in early life, even though seizures may not commence until adolescence or adulthood. Amongst the range of early life factors implicated in MTLE causation (febrile seizures, traumatic brain injury, etc.), stress may be one important contributor. Early life stress is an a priori agent deserving study because of the large amount of neuroscientific data showing enduring effects on structure and function in hippocampus and amygdala, the key structures involved in MTLE. An emerging body of evidence directly tests hypotheses concerning early life stress and limbic epilepsy: early life stressors, such as maternal separation, have been shown to aggravate epileptogenesis in both status epilepticus and kindling models of limbic epilepsy. In addition to elucidating its influence on limbic epileptogenesis itself, the study of early life stress has the potential to shed light on the psychiatric disorder that accompanies MTLE. For many years, psychiatric comorbidity was viewed as an effect of epilepsy, mediated psychologically and/or neurobiologically. An alternative – or complementary – perspective is that of shared causation. Early life stress, implicated in the pathogenesis of several psychiatric disorders, may be one such causal factor. This paper aims to critically review the body of experimental evidence linking early life stress and epilepsy; to discuss the direct studies examining early life stress effects in current models of limbic seizures/epilepsy; and to suggest priorities for future research.